How Do Thresholds of Principle and Preference Influence Surgeon Assessments of Learner Performance?. Issue 2 (August 2018) - Apramian, Tavis; Cristancho, Sayra; Sener, Alp; Lingard, Lorelei
Abstract : Objective: The present study asks whether intraoperative principles are shared among faculty in a single residency program and explores how surgeons' individual thresholds between principles and preferences might influence assessment. Background: Surgical education continues to face significant challenges in the implementation of intraoperative assessment. Competency-based medical education assumes the possibility of a shared standard of competence, but intersurgeon variation is prevalent and, at times, valued in surgical education. Such procedural variation may pose problems for assessment. Methods: An entire surgical division (n = 11) was recruited to participate in video-guided interviews. Each surgeon assessed intraoperative performance in 8 video clips from a single laparoscopic radical left nephrectomy performed by a senior learner (>PGY5). Interviews were audio recorded, transcribed, and analyzed using the constant comparative method of grounded theory. Results: Surgeons' responses revealed 5 shared generic principles: choosing the right plane, knowing what comes next, recognizing normal and abnormal, making safe progress, and handling tools and tissues appropriately. The surgeons, however, disagreed both on whether a particular performance upheld a principle and on how the performance could improve. This variation subsequently shaped their reported assessment of the learner's performance. Conclusions: The findings of the present study provide the first empirical evidence to suggest that surgeons' attitudes toward their own procedural variations may be an important influence on the subjectivity of intraoperative assessment in surgical education. Assessment based on intraoperative entrustment may harness such subjectivity for the purpose of implementing competency-based surgical education. Abstract : Supplemental Digital Content is available in the text